2021
DOI: 10.1136/emermed-2020-209992
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department attendances during the COVID-19 pandemic: a retrospective analysis of attendances following Irish governmental pandemic measures

Abstract: BackgroundCOVID-19 has resulted in the death of over 1 million people to date. Following government-implemented regulations, there has been concern over the apparent decline in emergency department (ED) attendances and the resultant health legacy. Therefore, we aimed to characterise the attendances to an Irish tertiary hospital ED following the implementation of these regulations during the COVID-19 pandemic.MethodsThis retrospective observational study investigated all attendances to the Cork University Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…They reported a decrease of the number of major trauma patients by 28%, with an associated decrease in workplace accidents, traffic accidents and sports injuries. Comparable developments were also confirmed by international studies [ 9 12 ]. However, different studies reported on some specificities.…”
Section: Discussionsupporting
confidence: 64%
“…They reported a decrease of the number of major trauma patients by 28%, with an associated decrease in workplace accidents, traffic accidents and sports injuries. Comparable developments were also confirmed by international studies [ 9 12 ]. However, different studies reported on some specificities.…”
Section: Discussionsupporting
confidence: 64%
“…In the initial period of the pandemic, individuals were hesitant about attending emergency departments or general practitioners. In some jurisdictions, people were actively discouraged from attending these services unless they were extremely unwell (Sless et al, 2021). Therefore, it is possible that referral rates for psychotic disorders during the pandemic may initially have declined due to a delay in help seeking, but may have been followed by a subsequent upswing in presentations characterised by a longer duration of untreated psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…1 A similar decrease in ED attendance has been reported in other countries, for example, Ireland, 2 Italy 3 and the USA. 4 While the decreasing attendance could have been to lower rates of infection by other viruses and/or injuries due to lockdown, 5 such a drop might be related to people avoiding EDs for fear of COVID-19. 6 This created concern that patients with potentially serious conditions might not attend EDs during the pandemic, potentially worsening their condition in the long run.…”
Section: Introductionmentioning
confidence: 99%